Capital structure and financial sustainability: stakes of microfinance institutions in Bamenda, Cameroon - Dobdinga Cletus Fonchamnyo; Tony Anyangwe; Ndichia Nana Chantal; Gildas Dohba Dinga (Future Business Journal, 2023)
Abstract This research assesses the effect of capital structure on the sustainability of Microfinance Institutions (MFIs) in Bamenda, Cameroon. We use panel data obtained from audited annual financial statements of fifteen (15) MFIs, comprising both member- and shareholder-owned MFIs in Bamenda, Cameroon from 2014 to 2020, and an ex-post facto causal research design. Debt, equity, grants, and retained earnings are used to capture capital structure, while Operational Self-Sufficiency is used as a proxy for sustainability. The Generalised Least Squares and the quantile-on-quantile techniques are used for data analysis. Our findings indicate a statistically significant negative relationship between debt, grants and financial sustainability of MFIs, while a statistically significant positive relationship is found between retained earnings and financial sustainability of MFIs. A positive, though statistically insignificant relationship is found between equity or share capital and MFI financial sustainability. The results are robust upon consideration of different quantiles. Based on the findings, MFIs in Cameroon should rely more on retained earnings and equity to be more financially sustainable. The findings additionally provide evidence relating to the shortcoming of grants in the financing of development initiatives.